Pengembangan Website Perpustakaan menggunakan Agile Software Development - Saputra, Darwin; Theng, Arifin; Hermanto, Dedy (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2023)
SD Muhammadiyah 10 Palembang as an educational service with a travel time of 19 minutes from Jalan Jenderal Ahmad Yani, Palembang.  Library facilities attract students because of the availability of the latest books.  However, the current system has not been able to manage collections properly. Upgrading the latest system becomes a competitiveness to create the latest and agility of the website system. The development of website systems has experienced technological development by 61.9% in the last 10 decades.  The change of HTML to javascript is a challenge in the development of this system.  An agile website is the main solution to facilitate library services. The features that users need and functionality become the right solution. Case study design becomes the main approach, because it adopts realistic conditions. Designing use case and entity relationship diagrams as technical to visualize and structure the features needed. Respondents in charge of testing when the prototype is ready to run. The success of the website prototype is tested through the pieces approach.  The development of agile website systems has been successfully tested. Javascript as a programming language does not experience errors.  This has proven that the development of the website is true and the development conditions have been able to manage the collection well according to the features needed by users. The library website of SD Muhammadiyah 10 Palembang has been successfully used, thus increasing the attractiveness for prospective students in the future.